Post-fire resprouting ability in young plants of Astronium fraxinifolium - Leite, Marilaine Cristina Marques [UNESP]; Leal, Alice Souza [UNESP]; Araujo, Maycon Anderson [UNESP]; Martins, Aline Redondo [UNESP] (CSIRO Publishing, 2022)
Fire is an important ecological factor that influences the composition of the Cerrado vegetation in Brazil. In environments where fire is recurrent, tree species with seedlings/saplings that accumulate underground reserves and/or present distinctive underground structures (tuberous roots and root crowns) are more likely to reach maturity. Astronium fraxinifolium Schott is a tree species native to the Cerrado. The tree has xeromorphic characteristics, which perhaps is an adaptation to dry and rocky environments. To evaluate whether these morphological characteristics allow the species to recover from fire, an experiment was conducted where we compared burnt and unburnt saplings of A. fraxinifolium. We verified the emergence of buds closer to the root crown and compared the storage dynamics of lipids, starch, phenolic compounds, and mucilage between the burnt and unburnt saplings. Buds were observed in some of the individuals within 7 days of burning. The burnt saplings showed a high survival rate of 77.8%. Two cotyledonary buds per plant originated from the base of the stem. The rapid recovery of the species could be attributed to the starch reserves in the stems and roots, which helped nourish the buds and the resprouted seedlings. The results of our study showed the resprouting ability of A. fraxinifolium as a survival mechanism in response to fire events.
Keywords: accumulation of reserves; bud bank; cotyledon buds; fire; gonçalo-alves; plant anatomy; plant structure; sprouting